New perspectives for the evaluation of training sessions in self-regulated learning: Time-series analyses of diary data - Schmitz, Bernhard; Wiese, Bettina S. (Contemporary educational psychology, 2006)
The present study combines a standardized diary approach with time-series analysis methods to investigate the process of self-regulated learning. Based on a process-focused adaptation of Zimmerman’s (2000) learning model, an intervention (consisting of four weekly training sessions) to increase self-regulated learning was developed. The diaries were applied to evaluate this intervention. A sample of 40 civil engineering students participated and 21 of them answered questions in standardized diaries over a five-week period. The effectiveness of the intervention was demonstrated using trend analyses that evinced significant improvements in self-regulatory behavior. In addition, interrupted time-series analyses and control group comparisons confirmed essential treatment effects. The results demonstrate the advantages of using standardized diaries to obtain ecologically valid data on daily learning.